2019
DOI: 10.1080/15384101.2019.1624111
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Up-regulated lncRNA5322 elevates MAPK1 to enhance proliferation of hair follicle stem cells as a ceRNA of microRNA-19b-3p

Abstract: Yin (2019) Upregulated lncRNA5322 elevates MAPK1 to enhance proliferation of hair follicle stem cells as a ceRNA of microRNA-19b-3p,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(45 reference statements)
4
9
0
Order By: Relevance
“…In the present study, we found that miR-214-3p can directly inhibit the expression of MAPK1, and the dual-luciferase reporter genes also confirmed the direct binding between miR-214-3p and MAPK1 gene. Cai et al showed that MAPK1 could promote HFSc proliferation, wound contraction and epidermal regeneration of mouse model [20]. Consistent with the previous study, we found that inhibition of miR-214-3p could induce HFSc differentiation, while inhibition of MAPK1 can reverse this effect, suggesting that MAPK1, as a downstream effector molecule of miR-214-3p, plays a role in promoting HFSc differentiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found that miR-214-3p can directly inhibit the expression of MAPK1, and the dual-luciferase reporter genes also confirmed the direct binding between miR-214-3p and MAPK1 gene. Cai et al showed that MAPK1 could promote HFSc proliferation, wound contraction and epidermal regeneration of mouse model [20]. Consistent with the previous study, we found that inhibition of miR-214-3p could induce HFSc differentiation, while inhibition of MAPK1 can reverse this effect, suggesting that MAPK1, as a downstream effector molecule of miR-214-3p, plays a role in promoting HFSc differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…4A). More importantly, Cai et al showed that MAPK1 promotes HFSc proliferation, wound contraction and epidermal regeneration in mouse model [20]. Here, we found the expression of MAPK1 was significantly increased in HFSc by differentiation at 7d and 14d (Fig.…”
Section: The Mir-214-3p Inhibits Adipogenic Differentiation Of Hfsc Bsupporting
confidence: 59%
“…In the present study, we found that miR-214-3p can directly inhibit the expression of MAPK1, and the dual-luciferase reporter gene assay also confirmed the direct binding between miR-214-3p and MAPK1 gene. Cai et al showed that MAPK1 could promote HFSc proliferation, wound contraction, and epidermal regeneration of mouse model [23]. Consistent with the previous study, we found that inhibition of miR-214-3p could induce HFSc differentiation, while inhibition of MAPK1 can reverse this effect, suggesting that MAPK1, as a downstream effector molecule of miR-214-3p, plays a role in promoting HFSc differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…4 a). More importantly, Cai et al showed that MAPK1 promotes HFSc proliferation, wound contraction, and epidermal regeneration in mouse model [ 23 ]. Here, we found the expression of MAPK1 was significantly increased in HFSc by differentiation on the 7th day and the 14th day (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, miR-19b was up-regulated in HG-treated hRMECs, and miR-19b overexpression dramatically inhibited cell viability and enhanced cell apoptosis and inflammation. Similarly, according to Cai's study, inhibition of miR-19b could promote the proliferation of hair follicle stem cells (HFSCs) [21]. All these studies supported our findings.…”
Section: Discussionsupporting
confidence: 87%